Gambaran Audiometri Pada Pasien Omsk Maligna Dengan Kolesteatoma di RSUP Fatmawati - Fasyah, Ismail fasyah (Sanus Medical Journal, 2024)
Otitis media supuratif kronis (OMSK) adalah peradangan pada telinga tengah yang sering terkait dengan kolesteatoma. Penelitian ini menganalisis audiometri pada pasien OMSK Maligna dengan kolesteatoma, mencakup derajat dan jenis ketulian, serta usia dan jenis kelamin. Menggunakan metode deskriptif analitik dengan data sekunder dari RSUP Fatmawati (2017-2021) dengan 215 sampel, hasil menunjukkan bahwa 64% pasien mengalami Conductive Hearing Loss, dan 31% Mix Hearing Loss. Ketulian paling umum adalah kategori sedang berat (30%), terjadi lebih banyak pada usia remaja akhir (17–25) dan dewasa awal (26–35), dengan perempuan lebih banyak terdiagnosis (55%). Chronic suppurative otitis media (CSOM) is an inflammation of the middle ear often associated with cholesteatoma. This study analyzes audiometry in patients with malignant CSOM and cholesteatoma, including the degree and type of hearing loss, as well as age and gender. Using a descriptive analytic method with secondary data from RSUP Fatmawati (2017-2021) involving 215 samples, the results show that 64% of patients experience conductive hearing loss, and 31% have mixed hearing loss. The most common hearing loss is in the moderate-severe category (30%), occurring more frequently in late adolescence (17–25) and early adulthood (26–35), with more females diagnosed (55%).   Chronic suppurative otitis media (CSOM) is an inflammation of the middle ear often associated with cholesteatoma. This study analyzes audiometry in patients with malignant CSOM and cholesteatoma, including the degree and type of hearing loss, as well as age and gender. Using a descriptive analytical method with secondary data from Fatmawati Hospital (2017-2021) with 215 samples, the results showed that 64% of patients experienced Conductive Hearing Loss, and 31% Mixed Hearing Loss. The most common deafness was moderate to severe (30%), occurring more in late adolescence (17–25) and early adulthood (26–35), with women being diagnosed more often (55%). Chronic suppurative otitis media (CSOM) is an inflammation of the middle ear often associated with cholesteatoma. This study analyzes audiometry in patients with malignant CSOM and cholesteatoma, including the degree and type of hearing loss, as well as age and gender. Using a descriptive analytic method with secondary data from RSUP Fatmawati (2017-2021) involving 215 samples, the results show that 64% of patients experience conductive hearing loss, and 31% have mixed hearing loss. The most common hearing loss is in the moderate-severe category (30%), occurring more frequently in late adolescence (17–25) and early adulthood (26–35), with more females diagnosed (55%).